Randomised controlled trial of diazoxide for small for gestational age neonates with hyperinsulinaemic hypoglycaemia provided early hypoglycaemic control without adverse effects. (28th February 2018) - Balachandran, Binesh; Mukhopadhyay, Kanya; Sachdeva, Naresh; Walia, Rama; Attri, Savita Verma
Abstract: Aim: Hyperinsulinaemic hypoglycaemia (HH) is a very common cause of hypoglycaemia in small for gestational age (SGA) neonates. We compared using early oral diazoxide or a placebo for this patient group. Methods: This was a randomised, double‐blind, placebo‐controlled trial that focused on SGA neonates born at at least 32 weeks of gestation with HH during the first five days of life. Neonates with severe perinatal asphyxia, sepsis or contraindications for oral feeds were excluded. The primary outcome was the hours taken to achieve hypoglycaemic control, with a glucose infusion rate of ≤4 mg/kg/min. The secondary outcomes were the duration of intravenous fluids, sepsis episodes, time to achieve full feeds and mortality. Results: We screened 490 neonates and 30 neonates were eligible for randomisation and completed the trial. Half received diazoxide and half received a placebo. The median time to achieve hypoglycaemia control (40 vs 71.5 hours, p = 0.015), the total duration of intravenous fluids (114 vs 164 hours, p = 0.04) and time to achieve full feeds (74 vs 124 hours, p = 0.02) were significantly lower in the diazoxide group, with no adverse effects attributed to the drug. Conclusion: Using oral diazoxide for SGA neonates with HH provided early hypoglycaemic control with no apparent adverse effects.